Myocardial Infarction after Long-Term Treatment with a Tyrosine Kinase Inhibitor (TKI) with Anti-VEGF Receptor Activity - L. Paschke; T. Lincke; K. Mühlberg; Tom H. Lindner; R. Paschke (Case Reports in Endocrinology)
TKIs including anti-VEGF receptor activity have been approved for the treatment of patients with radioiodine resistant thyroid carcinomas. For lenvatinib arterial thromboembolic events are listed as adverse events of special interest with lenvatinib. In the phase III study, arterial thromboembolic events were reported in 3% of lenvatinib-treated patients and 1% in the placebo group. Most of the patients had predisposing factors. Only one myocardial infarct was reported in the lenvatinib phase III study. We report a 73-year-old female patient with metastatic thyroid papillary carcinoma who was treated with total thyroidectomy. The operation was followed by four radioiodine therapies over a period of 6 years. At 6 years she developed lung metastasis without radioiodine uptake, one solitary liver metastasis and one solitary right renal metastasis. One year after the first diagnosis of radioiodine resistant lung metastasis the lung metastasis showed progression according to RECIST criteria. This treatment was resulting in prolonged partial response with disappearance of a hepatic and renal metastasis. A myocardial infarction occurred after 39 months of lenvatinib treatment resulting in implantation of 3 stents and a two chamber pacemaker. The treatment was discontinued. Except for well controlled hypertension there were neither predisposing diseases like diabetes nor symptoms of cardiac ischemia on exertion. However, the family history for cardiovascular diseases was positive for cardiac infarction reported for one brother. Another brother was treated for hypertension and the patient’s mother suffered from a cerebral infarction at the age of 60. While only one myocardial infarct was reported in the lenvatinib phase III study with 392 patients this case suggests that long-term treatment with lenvatinib may be associated with an increased risk for myocardial infarct also in patients with no predisposing diseases except well controlled hypertension and positive family history for cardiovascular diseases.